Insights into a rutile/brookite homojunction of titanium dioxide: separated reactive sites and boosted photocatalytic activity. Issue 63 (11th November 2019) - Chen, Jing; Guan, Meili; Zhang, Xuan; Gong, Xuezhong
Abstract : Reactive sites for redox reactions were spatially separated using a rutile/brookite homojunction, thus contributing to improved charge separation efficiency. Abstract : Benefiting from studies into Degussa TiO2, forming junctions via combining different phases of a semiconductor may provide new insights into the design of efficient photocatalysts, which are a key element in current solar-driven fuel production and environmental remediation. In this work, we aimed at creating a highly efficient rutile/brookite homojunction through precise crystal phase control. Characterization of the morphology and structure revealed that the ultrafine brookite phase TiO2 particles were uniformly attached to the surfaces of the rod-like rutile phase, not only readily forming a homojunction but also stabilizing the brookite phase. Surprisingly, the rutile/brookite-TiO2 homojunction exhibited a synergetic effect, improving the photocatalytic activity for both hydrogen generation and organic dye degradation. This was attributed to the well-matched band alignment and separated reaction sites, effectively promoting the charge separation efficiency. These results highlight the potential for bifunctional photocatalyst design with separated reactive sites for simultaneous redox reactions.